MicroRNA-488 inhibits tongue squamous carcinoma cell invasion and EMT by directly targeting ATF3 - Shi, Bingxia (Cell Mol Biol Lett, 2018)
BACKGROUND: It has been reported that the expression of activating transcription factor 3 (ATF3) is closely associated with both microRNA (miRNA) processing and the progress of many cancers. Our study aimed to explore the interaction between ATF3 and miR-488 in tongue squamous cell carcinoma (TSCC). METHODS: Quantitative real-time PCR was performed to detect the levels of ATF3 and miR-488 in TSCC tissues and cell lines. Cell invasion and epithelial–mesenchymal transition (EMT) were assessed to determine the biological functions of miR-488 and ATF3 in TSCC cells. The mRNA and protein levels of ATF3 were measured using quantitative RT-PCR and western blotting. Luciferase assays were performed to validate ATF3 as an miR-488 target in TSCC cells. RESULTS: We found that the level of miR-488 significantly decreased and the expression of ATF3 significantly increased in TSCC tissues and cell lines. A low level of miR-488 was closely associated with increased expression of ATF3 in TSCC tissues. Introducing miR-488 significantly inhibited the invasion and EMT of TSCC cells, and knockdown of miR-488 promoted both processes. The bioinformatics analysis predicted that ATF3 is a potential target gene of miR-488. The luciferase reporter assay showed that miR-488 could directly target ATF3. ATF3 silencing had similar effects to miR-488 overexpression on TSCC cells. Overexpression of ATF3 in TSCC cells partially reversed the inhibitory effects of the miR-488 mimic. CONCLUSION: miR-488 inhibited cell invasion and EMT of TSCC cells by directly downregulating ATF3 expression.